Analysis of thyroid malignant pathologic findings identified during 3 rounds of screening (1997‐2008) of a cohort of children and adolescents from belarus exposed to radioiodines after the Chernobyl accident. Issue 3 (28th October 2014) - Zablotska, Lydia B.; Nadyrov, Eldar A.; Rozhko, Alexander V.; Gong, Zhihong; Polyanskaya, Olga N.; McConnell, Robert J.; O'Kane, Patrick; Brenner, Alina V.; Little, Mark P; Ostroumova, Evgenia; Bouville, Andre; Drozdovitch, Vladimir; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Recent studies of children and adolescents who were exposed to radioactive iodine‐131 (I‐131) after the 1986 Chernobyl nuclear accident in Ukraine exhibited a significant dose‐related increase in the risk of thyroid cancer, but the association of radiation doses with tumor histologic and morphologic features is not clear. METHODS A cohort of 11, 664 individuals in Belarus who were aged ≤18 years at the time of the accident underwent 3 cycles of thyroid screening during 1997 to 2008. I‐131 thyroid doses were estimated from individual thyroid activity measurements taken within 2 months after the accident and from dosimetric questionnaire data. Demographic, clinical, and tumor pathologic characteristics of the patients with thyroid cancer were analyzed using 1‐way analysis of variance, chi‐square tests or Fisher exact tests, and logistic regression. RESULTS In total, 158 thyroid cancers were identified as a result of screening. The majority of patients had T1a and T1b tumors (93.7%), with many positive regional lymph nodes (N1; 60.6%) but few distant metastases (M1; <1%). Higher I‐131 doses were associated with higher frequency of solid and diffuse sclerosing variants of thyroid cancer (P < .01) and histologic features of cancer aggressiveness, such as lymphatic vessel invasion, intrathyroidal infiltration, and multifocality (all P < .03). Latency was not correlated with radiation dose. Fifty‐two patients with self‐reported thyroid cancers which were diagnosed before 1997 were younger at the time of the accident and had a higher percentage of solid variant cancers compared with patients who had screening‐detected thyroid cancers (all P < .0001). CONCLUSIONS I‐131 thyroid radiation doses were associated with a significantly greater frequency of solid and diffuse sclerosing variants of thyroid cancer and various features of tumor aggressiveness. Cancer 2015;121:457–466. © 2014 American Cancer Society.